Students’ Perception on Utilizing Kahoot! as a Game-Based Student Response System for EFL Students - Kurniawan, Aditya Bima; Unsiah, Frida; Razali, Khairil Azwar (JOLLT Journal of Languages and Language Teaching, 2024)
The utilization of mobile devices has significantly enhanced the EFL learning process. To accomplish so, student response systems (SRS) are often utilized in large classroom to gather studentsâ€™ responses immediately through wireless networking and facilitate the management and monitoring of learner engagement and comprehension. The objective of the current study is to investigate the perceptions of junior school EFL students regarding the utilization of Kahoot! as a Game-Based Student Response System (SRS). Sixty seven high school students attended an English lesson accompanied by Kahoot, an online game-based Student Response System. The researchers conducted interviews to investigate students’ perceptions of the expectation, advantages, and disadvantages of utilizing Kahoot!. Furthermore, classroom observations were conducted to get more comprehensive information. The result showed that the participants experienced advantages of utilizing Kahoot, such as the materials are easier to understand, the activities are engaging to do, and the studentsâ€™ motivation get increased. However, lack of device support, unstable internet connectivity, and focus distraction have become major challenges. It is implied that Kahoot! is recommended as a gamification to teach EFL students.